2013
DOI: 10.1136/bjsports-2012-091999
|View full text |Cite
|
Sign up to set email alerts
|

Injury situations in Freestyle Ski Cross (SX): a video analysis of 33 cases

Abstract: We identified four main injury situations in elite SX, dominated by jumping situations. The primary cause of injury was unintentional skier-opponent contact in jumping, bank turning and roller situations. Another common cause of injury was personal errors (inappropriate technique and strategy) at take-off and in turning situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 14 publications
(30 reference statements)
0
13
0
1
Order By: Relevance
“…Likewise, in recreational freestyle skiing and snowboarding, it has been found that the rate of severe injuries, in the form of spine and head injuries, is double inside terrain parks compared with outside 78. Furthermore, it has recently been demonstrated that a preponderance of the injuries occur in jumps, kickers and the halfpipe, in other words, in features that facilitate aerial manoeuvers 45 48 79 80. In order to mitigate the risk of these injuries, we need more refined data on their sport-specific risk factors and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in recreational freestyle skiing and snowboarding, it has been found that the rate of severe injuries, in the form of spine and head injuries, is double inside terrain parks compared with outside 78. Furthermore, it has recently been demonstrated that a preponderance of the injuries occur in jumps, kickers and the halfpipe, in other words, in features that facilitate aerial manoeuvers 45 48 79 80. In order to mitigate the risk of these injuries, we need more refined data on their sport-specific risk factors and mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 19 injuries in these disciplines, 6 resulted in an estimated absence of more than 2 weeks (fractures, contusions, distortions). As these athletes expose themselves to aerial manoeuvres and jump-landing tasks under high-speed conditions (slopestyle) or compete in heats with considerably risk-taking attitudes (cross),36 46 47 the occurrence of more severe injuries happening is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Cross disciplines are a motocross-inspired mixture of freestyle and alpine events, characterised by courses which include banks, compressions, jumps and giant slalom-type turns 16. Recent video analyses have revealed that the main injury situations in both cross disciplines involved jumping 17 18…”
Section: Discussionmentioning
confidence: 99%